Konstruksi Kohabitasi Dalam Film Pendek "Kisah Tiga Tahun" - Yulianti Dwi Cahyani; Tangguh Okta Wibowo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
Cohabitation is a term used for couples who live in the same house without marriage ties and cohabitation is widely constructed in various mass media products including the short film Kisah Tiga Tahun. This study aims to find out how the construction of cohabitation is shown in the short film Kisah Tiga Tahun. This study uses the theory of social reality construction and a qualitative approach and uses Roland Barthes' semiotic analysis technique, with his idea known as two orders of signification which includes denotation, connotation, and myth. The results of the analysis of this study indicate that the construction of cohabitation living together as a husband and wife is carried out based on the life experiences of unmarried lovers to explore each other's character. Cohabitation is also a husband and wife activity like a small family that has a harmonious relationship.